2021
DOI: 10.31234/osf.io/yhw3u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

I do not need to wash my hands because I will go to Heaven anyway: A study on belief in God and the afterlife, death anxiety, and COVID-19 protective behaviors

Abstract: This study examined the relationship between religious beliefs and protective behaviors during the COVID-19 pandemic. A study was conducted with 551 Polish participants. According to structural equation modeling analysis, being a believer is positively associated with belief in an afterlife, which, like death anxiety, but independent of it, is associated with perceiving COVID-19 as a non-severe disease, which is associated with low fear of COVID-19, and disregard for protective behaviors. Thus, our results all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Drawing on these multiple theoretical perspectives, we would argue that while preventative behavior in response to the pandemic may be influenced by an individuals' appraisal of the risk of contagion, they are unlikely to engage in protective actions, such as the consumption of a healthier diet, when they underestimate the severity of the threat or are less fearful of being personally affected by external events. Such behavior is likely to be observed for instance, in individuals with low death anxiety, perhaps due to religious beliefs in a better afterlife that reduces their fear of death (Drążkowski and Trepanowski, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Drawing on these multiple theoretical perspectives, we would argue that while preventative behavior in response to the pandemic may be influenced by an individuals' appraisal of the risk of contagion, they are unlikely to engage in protective actions, such as the consumption of a healthier diet, when they underestimate the severity of the threat or are less fearful of being personally affected by external events. Such behavior is likely to be observed for instance, in individuals with low death anxiety, perhaps due to religious beliefs in a better afterlife that reduces their fear of death (Drążkowski and Trepanowski, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…One group hesitant to vaccinate against COVID-19 may be religious people. Some studies have demonstrated that religious people defy and ignore governmental recommendations on protective behavior during the COVID-19 pandemic (Dein et al, 2020;Drążkowski & Trepanowski, 2021;Kranz et al, 2020;Milligan et al, 2021). Similarly, other recent studies have demonstrated that religiosity is negatively related to COVID-19 vaccination intention (Murphy et al, 2021;Olagoke et al, 2020).…”
Section: Introductionmentioning
confidence: 98%